Streptococcus intermedius Bacteremia and Liver Abscess following a Routine Dental Cleaning - Lachara V. Livingston; Elimarys Perez-Colon (Case Reports in Infectious Diseases)
Streptococcus intermedius is a member of the Streptococcus anginosus group of bacteria. This group is part of the normal flora of the oropharynx, genitourinary, and gastrointestinal tracts; however, they have been known to cause a variety of purulent infections including meningitis, endocarditis, and abscesses, even in immunocompetent hosts. In particular, S. intermedius has been associated with the development of liver and brain abscesses. There have been several case reports of S. intermedius liver abscesses with active periodontal infection. To our knowledge, however, there has not been a case following a routine dental procedure. In fact, the development of liver abscesses secondary to dental procedures is very rare in general, and there are only a few case reports in the literature describing this in relation to any pathogen. We present a rare case of S. intermedius bacteremia and liver abscess following a dental cleaning. This case serves to further emphasize that even routine dental procedures can place a patient at risk of the development of bacteremia and liver abscesses. For this reason, the clinician must be sure to perform a detailed history and careful examination. Timely diagnosis of pyogenic liver abscesses is vital, as they are typically fatal if left untreated.